STRATEGI PEMASARAN BIRO UMROH DAN HAJI PADA MASA PANDEMI COVID 19 - ani Nurul Imtihanah; Kukuh Cahyono (Multazam : Jurnal Manajemen Haji dan Umrah, 2021)
Hajj is part of the fifth pillar of faith after the creed, prayer, fasting, and alms. Hajj and Umrah are obligatory for those who are strong (able), every man or woman once in a lifetime. In general, the Indonesian Muslim community performs the Hajj and Umrah pilgrimages to the Grand Mosque in Mecca through Hajj and Umrah trips. The large number of Umrah pilgrims in Indonesia is the main attraction for entrepreneurs in the field of traveling. This study uses a qualitative approach and is a type of field research (Field Research) and compares the Hajj and Umrah services of PT. Makkah Multazam Safir and AlMadinah Tour & Travel in Bandar Lampung which together are business entities that provide services or providers of Hajj and Umrah services in the Baitullah. Two different data presentations will provide us with valid information about a program and services offered to prospective pilgrims in need. From the analysis that will be carried out, it will minimize errors in the future.